Unmet need for family planning services among young married women (15-24 years) living in urban slums of India - Kriti Yadav; Monika Agarwal; Mukesh Shukla; Jai Vir Singh; Vijay Kumar Singh (BMC, 2020)
Abstract Background NFHS-4 stated high unmet need for family planning (FP) among married women in Uttar Pradesh. Unmet need is highest among age groups: 15-19 and 20-24 years. Currently few data is available about unmet need for FP among vulnerable section of the community, i.e.15-24 year's age group living in the urban slums. Therefore this study was conducted to assess the unmet need for FP services and its determinants among this under-privileged and under-served section of society residing in urban slums of Uttar Pradesh, India. Methods Cross sectional study was conducted in the slums of Lucknow, India. One Urban-Primary Health Centre (U-PHC) was randomly selected from each of the eight Municipal Corporation zones in Lucknow and two notified slums were randomly selected from each U-PHC. All the households in the selected slums were visited for interviewing 33 young married women (YMW) in each slum, with a pre-structured and pre tested questionnaire, to achieve the sample size of 535. Analysis of the data was done using logistic regression. Results The unmet need for family planning services among YMW was 55.3%. About 40.9% of the unmet need was for spacing methods and 14.4% for limiting methods. Important reasons cited for unmet need for family planning services were negligent attitude of the women towards family planning, opposition by husband or others, embarrassment / hesitation / shyness for contraceptive use, poor knowledge of the FP method or availability of family planning services. Among method related reasons health concerns and fear of side effects were frequently cited reasons. On multiple logistic regression: age, educational status, duration of marriage, number of pregnancies, knowledge of contraceptive methods, opposition to contraceptive use and contact with Auxiliary Nurse Midwife (ANM) showed independently significant association with unmet need for family planning services. Conclusions Unmet need for family planning services is very high among the YMW of urban slums. The findings stress that program managers should take into cognizance these determinants of high level of unmet need for family planning among YMW and make intense efforts for addressing these issues in a holistic manner.